Guidelines for Implementing Imprisonment Sentences with Single Formulation (A Critique of Book I of the National Criminal Code) - Musa, M.; Zulhuda, Sonny; Endri, Endri; Susanti, Heni; Rinaldi, Kasmanto (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2024)
The most basic difference in the criminal system between the Criminal Code (WvS) and the National Criminal Code is the provision of sentencing guidelines. It is important to formulate guidelines for sentencing as a provision to achieve the objectives of punishment because they are related to the formulations of single and alternative penalties for criminal acts in the provisions of the National Criminal Code. This paper aims to conduct a theoretical study on the formulation of the criminal system from the guidelines for implementing prison sentences with a single formulation contained in Book I of the National Criminal Code, as a general rule that applies to Book II of the National Criminal Code and criminal law out of the National Criminal Code. The results of the study show that the formulation of criminal application guidelines with a single formulation contained in the provisions of Article 57 of the National Criminal Code theoretically does not follow the rules of the criminal system as they should. The provisions of Article 57 are placed in the 3rd paragraph to regulate